When does being in a talent pool reap benefits? The moderating role of narcissism. Issue 4 (8th August 2022) - Kanabar, Janki; Fletcher, Luke
ABSTRACT: Although talent pools are utilized by human resource development (HRD) practitioners to develop employees for future roles, their effectiveness is not guaranteed as individual differences may not be accounted for. To further understand why some individuals benefit more from talent development programmes than others, this study examines whether the positive effects of being in a talent pool on commitment and extra-role performance are mediated by organization-based self-esteem (OBSE), and to what extent these mediation paths are moderated by narcissism. Using a naturally occurring talent development initiative, 100 employees (N = 50 talent pool, N = 50 non-talent pool) in a UK bank were surveyed. An online questionnaire measured narcissism, OBSE, affective commitment, and extra-role performance. The results of the path analysis showed: a) talent pool employees had higher levels of OBSE, b) OBSE mediated the relationships between talent pool membership and outcomes, and c) narcissism weakened the relationship between talent pool membership and OBSE, such that it reduced the effect of the mediation pathways. Overall the findings suggest the need for differentiated talent strategies in organizations, particularly for those high in narcissism, and provides further avenues to examine the dark triad of personality traits in the field of HRD.